Measuring patient empowerment - A systematic review - Pekonen Arja; Eloranta Sini; Stolt Minna; Virolainen Petri; Leino-Kilpi Helena (Elsevier, 2022)
Objective: The purpose of this systematic review was to identify generic instruments measuring patient empowerment and related concepts and analyse the main content and psychometric properties of these instruments.
Methods: A systematic search was conducted using empowerment and related concepts (enablement, activation, engagement, perceived control) as search terms. The main content of the instruments was analysed by classifying the subscales and items of the elements of empowerment into patient’s capacities, patient’s knowledge, patient’s behaviour and support by others. Psychometric properties were analysed with the criteria of Terwee and colleagues (2007).
Results: Thirteen instruments were identified; and out of them, five instruments covered all the four elements used to define of empowerment. Psychometric properties were variable; none of the instruments contained all the evaluated psychometric properties.
Conclusion: There are generic instruments measuring empowerment and its related concepts. The instruments were heterogeneous in structure and psychometric properties. Empowerment is more wide-ranging and multidimensional than its related concepts.
Practice Implications: This review provides knowledge for healthcare professionals and researchers who want to support or evaluate patients’ empowerment. With a generic instrument, it is possible to obtain comparable information from diverse patient groups. Further testing of psychometric properties of each instrument is recommended.